'Credibility as a trade off' in electricity industries, a first evaluation. (24th August 2007) - Perez, Yannick
In the early 1990s, Pablo Spiller worked on North and Williamson's application of the New Institutional Economics, on the conditions of credible network reforms. Credibility is defined as the capacity to provide reform commitments. This work, started from a Positive Political Economics Veto Point Model, has been constructed and applied with good results. The Author will show the consequences of the 'credibility as a trade off' concept in the efficiency of Regulatory Instruments studied and then introduce two improvements. Self-Regulation is introduced and their performance reconsidered in order to achieve the trade off between commitment and flexibility.